Reconfiguration of technological and innovation capabilities in Mexican SMEs: Effective strategies for corporate performance in emerging economies - Luis Enrique Valdez-Juárez; Elva Alicia Ramos-Escobar; Edith Patricia Borboa-Álvarez (Administrative Sciences, 2023)
Latin American SMEs currently have serious financial and technological limitations. These problems have generated poor progress in technological digitization, innovation management, and corporate performance. The purpose of this research is to first analyze the direct effect that digitalization has on the management of innovation and corporate performance of Mexican SMEs. Secondly, the moderating effect that technological barriers have on the digitization, innovation, and results of the corporate performances of Mexican SMEs is examined. This study compiles information from a sample of 4121 managers of SMEs in the service trade and manufacturing sector. The information collection technique was through a personal interview (online questionnaire) addressed to the owner and/or manager of the SMEs through the LimeSurvey Professional platform. The fieldwork was carried out during the months of January to July of the year 2022. The structural equations model (SEM) was used for data analysis, specifically with the statistical technique of analysis of variance through the partial least square (PLS). The findings revealed that digitization has positive and significant effects on innovation management and corporate performance. In addition, the results indicate that the barriers to digitalization as a moderating variable have been impeding development and digital transformation and reducing the results of innovation and corporate performance of Mexican SMEs. This study contributes to the development of dynamic capabilities theory.
Keywords: 350; digital; innovation; performance; SMEs